Produksi dan Kualitas Susu Sapi Perah Penderita Mastitis yang Mendapat Pengobatan Antibiotik - Joko Riyanto; Sunarto Sunarto; Bayu Setya Hertanto; Muhammad Cahyadi; Rosyid Hidayah; Wahyu Sejati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2016)
This study aims to determine differences of production, the physical quality and chemical quality of dairy cattle mastitis patients before and after treatment with antibiotics penicillin-streptomycin. This research was conducted in farmer group (KTT) Subur Makmur, Banyuanyar Village, District Ampel, Boyolali. The material used is 15 cows PFH suffering from mastitis in lactation period 3rd trimester, aged 3 to 5 years. Combinations of antibiotics used is penicillin G 3 grams of mixed powder injection streptomycin sulfate injection of 1 gram powder is then dissolved with aquadestilata until volume of 15 ml. Antibiotics do 1 times a day for 5 days intramuscularly and intramammae. This research was carried out experimentally with two treatments and 15 replications. Data were analyzed by paired sample t-test (paired sample t-test). The analysis showed highly significant (P<0,01) on milk production, protein content, lactose, fat, nonfat dry (BKTL) and the Californian Mastitis Test (CMT), significant differences (P<0,05) pH, color, smell and consistency as well as the difference was not significant (P>0,05) against density. The conclusion of this research is the treatment of penicillin-streptomycin antibiotic use in dairy cows mastitis patients effectively improve the production, chemical quality and physical qualities but can not improve the density of milk. Keywords: mastitis, production, physical quality, chemical and bacteriological quality, milk, penicillin, streptomycin